Advances in tannic acid-incorporated biomaterials: Infection treatment, regenerative medicine, cancer therapy, and biosensing - ERSOY, SEZGİN (Elsevier B.V., 2022)
Polyphenol-based materials have attracted wide-spread interest from academic and industrial communities because of their unique structure and physicochemical properties. Tannic acid (TA), as a polyphenolic phytochemical with high level of galloyl groups, interacts with various substances (proteins, polysaccharides, and metals) through several modes including hydrogen bonding, hydrophobic and electrostatic interactions. Such hybrid or hybrid-like systems allow the preparation of various advanced materials with promising applications in medicine. In this review, we highlight the recent advances of TA-incorporated materials in medical applications including drug delivery, tissue engineering, treatment of infections, cancer therapy and biosensing. We believe that this review provides further investigation and development of TA as a promising natural compound to design new versatile architectures in the field of materials science. © 2021 Elsevier B.V.
Keywords: Antibacterial; Cancer therapy; Cytotoxicity; Polyphenol-based materials; Supramolecular interactions; Tannic acid